Religion, gender, and family violence : when prayers are not enough - Holtmann, Catherine (International studies in religion and society, 2018)
The chapters of Religion, Gender, and Family Violence: When Prayers Are Not Enough have been written from multiple disciplinary perspectives (sociology, religious studies, law) and based on research within diverse religious traditions including Christianity, Islam, and Judaism, as well as new religious movements. Similarities and differences between traditions are highlighted based on empirical research which shows how people actually deal with family violence in different contexts. This book also addresses some of the larger historical and political backgrounds that impact the experiences of family violence amongst ethno-religious minorities. The lives of religious victims and perpetrators of family violence are considered, as well as the responsibilities of religious leaders, congregations and secular professionals in addressing this widespread social problem.